1988
DOI: 10.1152/ajpcell.1988.254.3.c450
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-gold labeling of glycoconjugates in normal and Brattleboro rat papilla: effect of vasopressin

Abstract: Some reports suggest that the plasma membrane glycocalyx of collecting duct epithelial cells, as well as interstitial glycoconjugates, may be involved in vasopressin action and urinary concentration. In view of this, we have used the lectin-gold technique to map and quantify Helix pomatia lectin (HPL)-binding sites in the inner medulla of kidneys from normal Long-Evans rats, vasopressin-deficient Brattleboro rats, and Brattleboro rats treated for up to 5 wk with exogenous vasopressin. The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…8d; (312)]. Binding studies with various lectins have revealed distinct labeling patterns in rat and rabbit DTLs and ATLs (255,256,343,430). Structure-Function Correlations.…”
Section: Intermediate Tubulementioning
confidence: 99%
“…8d; (312)]. Binding studies with various lectins have revealed distinct labeling patterns in rat and rabbit DTLs and ATLs (255,256,343,430). Structure-Function Correlations.…”
Section: Intermediate Tubulementioning
confidence: 99%
“…In lectin-binding studies, we have found that the lower part of the descending thin limb of Henle shows apical labeling with Helix pomatia lectin and Dolichos biflorus lectins, whereas the thin ascending limbs are unlabeled (Weyer et al, 1987). Therefore, a differential lectin binding must be added to the inventory of other differences noted among thin limb segments.…”
Section: Thin Limbs Of Henle's Loopmentioning
confidence: 99%
“…In order to allow unlimited access of the lectin marker to intracellular structures, as well as cell surface components, lectin immunocytochemical studies have employed various tissue thicknesses (30 µm, 50 µm, 60 µm, 100 µm, less than 1 mm and 1 mm) in the pre-embedding procedure [27,28,29,30]. The current study made use of 1 mm initially and was subsequently adjusted to tissues of less than 1 mm thickness for pre-embedding.…”
Section: Thickness Of the Tissue Before Processingmentioning
confidence: 99%